The H protein of attenuated canine distemper virus is degraded via endoplasmic reticulum-associated protein degradation - Wang, Wenjie; Bi, Zhenwei; Liu, Yakun; Xia, Xingxia; Qian, Jing; Tan, Yeping; Zhao, Jianjun; Song, Suquan (Frontiers in Veterinary Science, 2023)
： Canine distemper (CD) caused by canine distemper virus (CDV) is considered as a highly contagious and acutely febrile disease in various animals around the world. Endoplasmic reticulum-associated protein degradation (ERAD)is an important biological effect induced by endoplasmic reticulum (ER) stress (ERS) for the degradation of unfolded/misfolded proteins in the ER of cells. CDV H glycoprotein is translocated into the ER for post-translational modifications. The effects of CDV H and ER on each other is unclear. In this study, we found that CDV H protein induced ERS through PERK-mediated signaling pathway. Inhibition of ERS by 4-Phenylbutyric acid (4-PBA) increased the H protein amounts of an attenuated CDV, which was reduced by dithiothreitol (DTT)-induced ERS. Further, the H protein levels were increased when ERAD was inhibited by using Eeyarestatin I or interfering E3 ligase Hrd1 in ERAD, suggesting that the attenuated CDV H protein is degraded via ERAD. ERAD involved ubiquitin-dependent proteasome degradation (UPD) and/or autophagic-lysosome degradation (ALD). The attenuated CDV H protein was ubiquitinated and significantly increased after treatment with UPD inhibitor MG132 but not ALD inhibitor chloroquine (CQ), suggesting that ERAD degrading the attenuated CDV H protein selectively depends on UPD. Moreover, the inhibition of degradation of CDV H protein with 4-PBA or MG132 treatment increased viral replication, whereas treatment with DTT promoting degradation of H protein was found to reduce viral replication. These findings suggest that the degradation of CDV H protein via ERAD negatively affects viral replication and providing a new idea for developing CDV prevention and control strategies.